2019
DOI: 10.1002/ijgo.12963
|View full text |Cite
|
Sign up to set email alerts
|

HPV self‐sampling acceptability and preferences among women living with HIV in Botswana

Abstract: Objective To assess the acceptability and preferences of HPV screening with self‐sampling and mobile phone results delivery among women living with HIV (WLWH) in Botswana, as an alternative to traditional speculum screening. Methods WLWH aged 25 years or older attending an infectious disease clinic in Gaborone were enrolled in a cross‐sectional study between March and April 2017. Women self‐sampled with a flocked swab, had a speculum exam, and completed an interviewer‐administered questionnaire about screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 22 publications
5
46
1
Order By: Relevance
“…In the current study, the majority of participants were comfortable self-collecting the sample using the SelfCerv applicator tampon. Consistent with previous studies, participants reported self-sampling as being painless when using nylon-tipped flocked swabs and flocked swabs [ 32 , 33 ] and comfortable when using self-sampling devices such as Evalyn brushes, flocked swabs, and Dacron swabs [ 9 , 33 , 34 ]. However, there were conflicting findings, since some of the participants who had reported self-sampling using the applicator tampon being comfortable but also reported experiencing pain.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, the majority of participants were comfortable self-collecting the sample using the SelfCerv applicator tampon. Consistent with previous studies, participants reported self-sampling as being painless when using nylon-tipped flocked swabs and flocked swabs [ 32 , 33 ] and comfortable when using self-sampling devices such as Evalyn brushes, flocked swabs, and Dacron swabs [ 9 , 33 , 34 ]. However, there were conflicting findings, since some of the participants who had reported self-sampling using the applicator tampon being comfortable but also reported experiencing pain.…”
Section: Discussionsupporting
confidence: 82%
“…And a significantly higher number of women gave positive feedback on favor of self-sampling, however, when it comes to their confidence of doing the test properly higher number of women reported that they would feel more comfortable of the results if it was performed by a clinician [ 23 26 , 30 ]. This was similar to the study done in Botswana, although the number was significantly high in favor of self-sampling when it comes to ease, comfort and preference, this was not the case when the women were asked if they felt confidence on doing the test properly [ 28 ]. Although a statistically significant majority of the participants preferred self-sampling, a proportion of them were concerned regarding their ability to collect the sample correctly and trusting the physician sampling.…”
Section: Discussionsupporting
confidence: 75%
“…Another review also shows that HPV self-sampling is highly accepted as the participants found it easy and convenient [22]. This was also reflected in observational studies [23][24][25][26][27][28][29][30]. Different observational studies conducted in sub-Saharan Africa assessed acceptance of self-sampling using different questions; ease of use of the device, the comfort, privacy, whether they would recommend to a friend, if they felt relaxed while using it, and if they felt confidence on doing the test properly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the challenges of introducing HPV testing, it is important to evaluate the opportunities for introducing HPV testing as the primary screening method in LMICs. In Sub-Saharan Africa, particularly South Africa, the majority of studies have investigated women's perceptions, acceptability, and preference of HPV self-sampling [19][20][21][22][23] in comparison to healthcare worker sampling. However, studies comparing the detection rate of HPV between healthcare worker-collected-and self-collected samples in LMICs are limited.…”
Section: Discussionmentioning
confidence: 99%